A 3D forward stratigraphic model of fluvial meander-bend evolution for prediction of point-bar lithofacies architecture. (August 2017) - Yan, Na; Mountney, Nigel P.; Colombera, Luca; Dorrell, Robert M.
Abstract: Although fundamental types of fluvial meander-bend transformations – expansion, translation, rotation, and combinations thereof – are widely recognised, the relationship between the migratory behaviour of a meander bend, and its resultant accumulated sedimentary architecture and lithofacies distribution remains relatively poorly understood. Three-dimensional data from both currently active fluvial systems and from ancient preserved successions known from outcrop and subsurface settings are limited. To tackle this problem, a 3D numerical forward stratigraphic model – the Point-Bar Sedimentary Architecture Numerical Deduction (PB-SAND) – has been devised as a tool for the reconstruction and prediction of the complex spatio-temporal migratory evolution of fluvial meanders, their generated bar forms and the associated lithofacies distributions that accumulate as heterogeneous fluvial successions. PB-SAND uses a dominantly geometric modelling approach supplemented by process-based and stochastic model components, and is constrained by quantified sedimentological data derived from modern point bars or ancient successions that represent suitable analogues. The model predicts the internal architecture and geometry of fluvial point-bar elements in three dimensions. The model is applied to predict the sedimentary lithofacies architecture of ancient preserved point-bar and counter-point-bar deposits of the middle Jurassic Scalby Formation (North Yorkshire, UK) to demonstrate the predictive capabilities of PB-SAND in modelling 3D architectures of different types of meander-bend transformations. PB-SAND serves as a practical tool with which to predict heterogeneity in subsurface hydrocarbon reservoirs and water aquifers. Graphical abstract: Highlights: PB-SAND, a numerical forward stratigraphic model, is devised. PB-SAND can predict 3D architecture of point bars developed by different meander-bend transformations. PB-SAND is applied to predict heterogeneous fluvial successions of Scalby Formation. PB-SAND can aid explorations of heterogeneity in subsurface reservoirs.